Android-based Rooftop Solar Power Plant Capacity Calculator Application Development - Olnes Yosefa Hutajulu; Muhammad Dominique Mendoza; Denny Haryanto Sinaga; Christin Erniati Panjaitan (Universitas Medan Area, 2023)
The utilization of solar energy to produce electrical energy in the form of a rooftop solar power generation system (PLTS) is an option to anticipate fossil energy scarcity and reduce pollution. The Indonesian government also urges the public to participate in using PLTS. However, until now there are only 4000 users throughout Indonesia. The main problem with the small number of PV mini-grid users is the difficulty of obtaining information related to the material requirements and costs for building a PV mini-grid system. Therefore, this research then proposes the creation of an application that can provide convenience for the community to calculate the capacity requirements of PLTS and its costs according to the electrical equipment that is operated as needed. This article contains the process of designing, manufacturing and testing an application for calculating the capacity and cost of a PV mini-grid. The design sprint method used in this research is in the design and manufacturing process. While the application testing uses the black box and usability testing. The final result of the testing process shows that with the black box testing method by 3 experts, it is known that all functions of the application are 100%